Marine Local Content Curriculum for Coastal Community: an Insight from Integrated Islamic Elementary School, Batam City (Universitas Negeri Semarang, 2022)
This study aims to obtain information related to the content of the marine curriculum in order to preserve the wisdom of coastal communities carried out at the SD IT Mahabbatul Haq Batam City. The research method uses descriptive qualitative research with a case study design. Data collection techniques with interviews, observation, and documentation. The results showed that 2 factors caused the lack of implementation of marine local content at SD IT Mahabbatul Haq Batam City. These factors consist of internal factors, namely administratively the SD IT Mahabbatul Haq Batam City does not yet have the necessary documents such as marine curriculum documents and Learning Implementation Plan (RPP). The implementation of marine local content learning is only guided by the syllabus of marine local content subjects. Meanwhile, external factors have not had a major impact on the surrounding coastal communities. In addition, 2 factors influence the reason why the application of local marine content in supporting the preservation of the wisdom of coastal communities, namely the environmental aspect, and the cultural aspect. Abstrak Penelitian ini bertujuan untuk memperoleh informasi terkait muatan kurikulum kelautan guna melestarikan kearifan masyarakat pesisir yang dilaksanakan di Sekolah Dasar IT Mahabbatul Haq Kota Batam. Metode penelitian menggunakan kualitatif deskriptif dengan desain penelitian studi kasus. Teknik pengumpulan data dengan wawancara, observasi dan dokumentasi. Hasil penelitian menunjukkan terdapat 2 faktor yang menyebabkan kekurangan dari pelaksanaan muatan lokal kelautan di SD IT Mahabbatul Haq Kota Batam. Faktor tersebut terdiri dari faktor internal yaitu secara administratif Sekolah Dasar IT Mahabbatul Haq Kota Batam belum memiliki dokumen yang diperlukan seperti dokumen kurikulum kelautan dan Rencana Pelaksanaan Pembelajaran (RPP) kelautan. Pelaksanaan pembelajaran muatan lokal kelautan hanya berpedoman pada silabus mata pelajaran muatan lokal kelautan. Sedangkan faktor eksternal berkaitan dengan belum berdampak besar terhadap masyarakat pesisir disekitarnya. Selain itu terdapat 2 faktor juga yang mempengaruhi alasan mengapa diterapkannya muatan lokal kelautan dalam mendukung pelestarian kearifan masyarakat pesisir yaitu segi lingkungan, dan segi kultural.